A nonuniform distributed power amplifier in 0.18‐mm CMOS technology. Issue 6 (30th March 2017) - Zhang, Ying; Ma, Kaixue; Zhang, Changchun; Zhang, Yi; Guo, Yufeng
ABSTRACT: A nonuniform distributed power amplifier (DPA) is designed and implemented in a 0.18 μm CMOS technology. To achieve high output power and efficiency in the wide frequency band, the impedance matching of T‐type networks is analyzed and the tapered on‐chip inductors of the output artificial transmission lines are designed. Non‐uniform gain cells together with the tapered on‐chip inductors are used to improve the output power while maintaining the good input and output impedance matchings. The chip size of the DPA is only 1.16 × 0.57 mm 2 including testing pads. The proposed DPA achieves 8.7 dB average associated gain from 1 to 19 GHz. The output power at 1‐dB output compression point (OP1dB ) is more than 7.6 dBm and the best power‐added efficiency (PAE) is 7.4% in the frequency band of 1–18 GHz. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1416–1420, 2017